Quantum Simulation for Studying High-Temperature Superconductors - Yasser Sayed; Ahmed Hossam; Mona Abdallah (Journal of Tecnologia Quantica, 2024)
High-temperature superconductors are a very interesting phenomenon because they can operate at much higher temperatures compared to conventional superconductors. However, the mechanism underlying superconductivity at high temperatures is still not fully understood. This study aims to study the properties of high-temperature superconductors through quantum simulations to identify factors that affect the critical temperature and phase stability of superconductors. The method used is quantum simulation using the Monte Carlo technique to model electron-interaction and magnetic fluctuations in various high-temperature superconducting materials, such as cuprates and iron-based superconductors. The results showed that strong electron interactions and optimal crystal structure played an important role in achieving high critical temperatures, while strong magnetic fluctuations could disrupt the stability of Cooper pairs and lower critical temperatures. This research contributes to a deeper understanding of the role of electron-interaction and magnetic fluctuations in high-temperature superconductivity, as well as opening up opportunities to design new materials with higher critical temperatures. The limitations of this study lie in the complexity of the system being studied, which requires large computing resources. Further research can be focused on the development of more efficient simulation algorithms and the application of physical experiments to validate the simulation results.